2008
DOI: 10.1136/jmg.2007.056366
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan for loci of musical aptitude in Finnish families: evidence for a major locus at 4q22

Abstract: Background:Music perception and performance are comprehensive human cognitive functions and thus provide an excellent model system for studying human behaviour and brain function. However, the molecules involved in mediating music perception and performance are so far uncharacterised.Objective:To unravel the biological background of music perception, using molecular and statistical genetic approaches.Methods: 15 Finnish multigenerational families (with a total of 234 family members) were recruited via a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(127 citation statements)
references
References 27 publications
13
111
1
2
Order By: Relevance
“…Multigenerational family studies were also able to demonstrate that predisposing genes or variants are linked to musical aptitude (e.g. Pulli et al, 2008). The link between musical aptitude and phonetic language abilities in this investigation shows that both faculties do not completely deviate from each other, which raises the idea that multigenerational family studies might yield similar results for phonetic aptitude which should be subject to future research.…”
Section: Music Perception: Tone Languages Versus Non-tone Languagesmentioning
confidence: 62%
“…Multigenerational family studies were also able to demonstrate that predisposing genes or variants are linked to musical aptitude (e.g. Pulli et al, 2008). The link between musical aptitude and phonetic language abilities in this investigation shows that both faculties do not completely deviate from each other, which raises the idea that multigenerational family studies might yield similar results for phonetic aptitude which should be subject to future research.…”
Section: Music Perception: Tone Languages Versus Non-tone Languagesmentioning
confidence: 62%
“…Of the families under study, 19 have been described earlier 8,18 and 12 are new ( Figure 1). The nationwide recruitment process of the families has been described earlier.…”
Section: Materials and Methods Participantsmentioning
confidence: 99%
“…20 The characteristics of the tests and testing procedure have been described in detail by Pulli et al 18 Shortly, KMT measures recognition of melodic contour, grouping, relational pitch processing and gestalt principles, the same potentially innate musical cognitive operations reported by Justus and Hutsler. 21 In contrast, the Seashore's tests measure simple sensory capacities, such as the ability to detect small differences in tone pitch or duration that are necessary in music perception.…”
Section: Music Testsmentioning
confidence: 99%
“…27 The participants neither reported any relatives in the study (based on a questionnaire) nor showed any close relatedness in identity by descent analysis. No medical information was available from the participants, but as far as we know, they are healthy.…”
Section: Study Materialsmentioning
confidence: 99%
“…[23][24][25][26] In this context, we characterized the genome-wide architecture of CNVs in 286 healthy, unrelated subjects characterized for musical aptitude and related traits. 27 We wanted to essentially evaluate the role of CNV enrichment in music-related phenotypes. In a broader perspective, the sample set represents the isolated Finnish population that has experienced multiple bottlenecks in its population history.…”
Section: Introductionmentioning
confidence: 99%